Weapons of Kamianka-Buska (Strumilowa) Castle in the First Half of the 16th Century - Hański, Oleg (Narzędzia wojny, 2023)
The Central Archives of Historical Records in Warsaw holds the documents containing information about the armament and fortification of royal castles on the eastern borders of the Kingdom of Poland, including the descriptions of cities and castles in the Lviv Land of the Ruthenian Voivodeship. In particular, the collection of manuscripts from years 1534 (2 registers) and 1542 (1 register) contains several pages of information about the weapons stored in the small castle in Kamionka Strumiłowa (since 1944 р. Kamionka– Buzka (Кам'янка-Бузька), currently a town in the Lviv Region in western Ukraine). The shorts synopsis comprises records only about castle weapons, artillery and stocks of ammunition. The purpose of this article is to show the state of artillery and small arms that were supposed to protect the inhabitants of Kamianka from the attacks of Tatars, Turks and Moldovans. According to the manuscripts, it appears that the castle artillery consisted of 4 bombards or veuglaires, 1 bronze cannon, 1 small fauconneau (półtarasnica), 1 mortar, 1 damaged fauconneau (taraśnica). The personal handfirearms of the defenders of Kamianka Buzka included a 4–7 handguns (rusznica) and 9 hackbut (hakownica). The garrison also had 12 crossbows and 2 tensioning mechanisms for the bow string (goats foot lever, hewar). Cold weapons appeared to be not popular, as the records mention only 4 bear spears (rohatina). The reserves of body armour were small and amounted to only 5 breastplates (plachy przednie) and 2 backplates (plachy zadnie) of cuirass. Artillery supplies were represented by bullets, gunpowder and tin.